A Review on the Advances of Biocompatible Materials and Their Processing Via Additive Manufacturing for Tissue Engineering Applications - Jassen Morales, Anuar; Domínguez López, Iván; Sosa Savedra, Julio Cesar; García García, Adrian Luis (Revista Mexicana de Ingenieria Biomedica, 2023)
About two decades ago, medicine experienced a revolutionary approach, driven by technological development in manufacturing techniques and scientific advances in the medical and life sciences, the field took on the challenge of regenerating tissue and organs damaged by disease, trauma, or hereditary issues, incorporating additive manufacturing as one of its strategies. Since its inception, regenerative medicine has developed techniques like tissue engineering, cellular therapy, medical devices, and artificial organs to provide wound healing and orthopedic applications. The incorporation of additive manufacturing allowed to recreate biologically appropriate environments for cell reproduction and growth that, eventually, lead to useful, regenerated tissue or organs. The objective of the present work is to review recent advances in the application of additive manufacturing techniques and ad hoc biomaterials in the field of regenerative medicine, to determine their impact in the development of new therapies for tissue engineering.